2021
DOI: 10.1021/acsaem.1c01769
|View full text |Cite
|
Sign up to set email alerts
|

Fe-Doped Copolymer-Templated Nitrogen-Rich Carbon as a PGM-Free Fuel Cell Catalyst

Abstract: Platinum group metal-free (PGM-free) catalysts present a promising opportunity to make hydrogen fuel cells more affordable; however, issues with stability and electrochemical activity continue to hinder their application. Recent studies point to the availability of nitrogen and a controlled mesoporous structure as avenues of improvement. To address this need, copolymer-templated nitrogen-enriched carbon (CTNC) was used as the precursor to prepare PGM-free catalysts for the oxygen reduction reaction (ORR). By e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Considering that Fe/N/C is a nonprecious catalyst, our results show for the first time that the cost/performance trade-off strongly favors Fe/N/C over Pt/C for desalination fuel cell applications. Given the richness of nonprecious metal catalysts investigated for classical fuel cell applications, this work opens up the field of desalination fuel cells to similar investigations. In the future, through wider materials explorations and optimization, we believe that nonprecious metal catalysts may outperform Pt in desalination fuel cells.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that Fe/N/C is a nonprecious catalyst, our results show for the first time that the cost/performance trade-off strongly favors Fe/N/C over Pt/C for desalination fuel cell applications. Given the richness of nonprecious metal catalysts investigated for classical fuel cell applications, this work opens up the field of desalination fuel cells to similar investigations. In the future, through wider materials explorations and optimization, we believe that nonprecious metal catalysts may outperform Pt in desalination fuel cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since its discovery, reversible-deactivation radical polymerization (RDRP) has been leveraged to access a wide variety of polymers that can be applied in various fields from biomedicine to informatics. The ability to precisely tune chemical and physical properties of macromolecules (e.g., molecular weight, architecture, functionality) has led to the deployment of RDRP for the synthesis of advanced materials across a wide range of size scales. While predetermined molecular weights are a defining feature of RDRP methods, such as atom transfer radical polymerization (ATRP), nitroxide mediated polymerization (NMP), and reversible addition–fragmentation chain transfer (RAFT) polymerization, targeting molecular weights in excess of 10 6 g/mol is challenging and typically requires specialized reaction conditions, such as high pressure. However, recent reports in RDRP have opened new synthetic pathways to access polymers of ultra-high chain length under mild reaction conditions . We recently demonstrated that long-wave ultraviolet (UV) irradiation (λ = 365 nm) of thiocarbonylthio compounds in the presence of vinyl monomers with high propagation rate constants ( k p ) in water can yield ultra-high molecular weight (UHMW) polymers with predictable molecular weights .…”
mentioning
confidence: 99%